STUDENT CHARACTER EDUCATION THROUGH THE IMPLEMENTATION OF RELIGIOUS MODERATION IN MADRASAH TSANAWIYAH - Ahmad Rifqi Azmi (Qouman : Jurnal Pendidikan dan Studi Islam, 2025)
The Qur'an is also believed to include this word as al-Salam (a term for Allah the Most Calm), muslim (a person who seeks a peaceful life), silm (harmony itself), Islam (a term for the religion sent by the Prophets). off lifting Allah's expression), so that humans live in harmony with themselves, their families, social networks, the grave, until they enter heaven "dār al-salam". The word welcome comes from Arabic which means harmony, peace and is used mainly as a description of respect. Conveys the meaning of a sense of security, but contains the essence of being free from all dependence and tension, so that life feels calm, serene and safe. Apart from the many parties who are against this appeal, there are also quite a few parties who are pro.